Sex differences in endocannabinoids during 3 years of Mediterranean diet intervention: Association with insulin resistance and weight loss in a population with metabolic syndrome - Soldevila-Domenech, Natalia; Pastor, Antoni; Sala-Vila, Aleix; Lázaro, Iolanda; Boronat, Anna; Muñoz, Daniel; Castañer, Olga; Fagundo, Beatriz; Corella, Dolores; Fernández-Aranda, Fernando; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; et al. (Frontiers in Nutrition, 2022)
Background: Excess circulating endocannabinoids (eCBs) and imbalanced N-acylethanolamines (NAEs) related eCBs abundance could influence dietary weight loss success. We aimed to examine sex differences in the impact of a 3-years Mediterranean diet (MedDiet) intervention on circulating eCBs, NAEs and their precursor fatty acids, and to analyze the interplay between changes in eCBs or NAEs ratios, insulin resistance and the achievement of clinically meaningful weight reductions. Methods: Prospective cohort study in a subsample of N=105 participants (54.3% women; 65.6±4.6 years) with overweight or obesity and metabolic syndrome that underwent a 3-years MedDiet intervention (PREDIMED-Plus study). Plasma eCBs and NAEs, including 2-arachidonoylglycerol (2-AG), anandamide (AEA), oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), fatty acids, diet, glycemic homeostasis (including the assessment of insulin resistance-HOMA-IR), and cardiovascular risk markers were monitored (at 0-6-12-36 months). Results: MedDiet adherence increased in both sexes and remained high during the 3 years of follow-up. Reductions in body weight, glycemic and cardiovascular parameters were larger in men than in women. Women presented higher concentrations of NAEs than men throughout the study. In both sexes, AEA and other NAEs (including OEA, and PEA) decreased after 6 months (for AEA: -4.9%), whereas the ratio OEA/AEA increased after 1 year (+5.8%). Changes in 2-AG (-3.9%) and the ratio OEA/PEA (+8.2%) persisted over the 3 years of follow-up. In women, 6-months changes in AEA (OR=0.65) and the ratio OEA/AEA (OR=3.28) were associated with the achievement of 8% weight reductions and correlated with HOMA-IR changes (r=0.29 and r=-0.34). In men, OEA/PEA changes were associated with 8% weight reductions (OR=2.62) and correlated with HOMA-IR changes (r=-0.32). Conclusions: A 3-years MedDiet intervention modulated plasma concentrations of eCBs and NAEs. Changes in AEA and in the relative abundance of NAEs were associated with clinically meaningful weight reductions. However, marked sex differences were identified in eCBs and NAEs, as well as in the efficacy of the intervention in terms of glycemic and cardiovascular parameters, which could be related to post-menopause alterations in glucose metabolism. These findings support a sex-balanced research strategy for a better understanding of the mechanisms underlying the regulation of body weight loss.